Energy storage mechanisms in vacancy-ordered Wadsley–Roth layered niobates. Issue 35 (11th August 2021) - McColl, Kit; Griffith, Kent J.; Dally, Rebecca L.; Li, Runze; Douglas, Jason E.; Poeppelmeier, Kenneth R.; Corà, Furio; Levin, Igor; Butala, Megan M.
Abstract : Layered niobates with vacancy-ordered Wadsley–Roth structures were investigated as Li-ion battery anodes. Using operando and ex situ methods and DFT, we identify an intercalation mechanism dominated by Li-diffusion kinetics and layer evolution. Abstract : Wadsley–Roth (WR) crystallographic shear structures demonstrate high energy and power densities as Li-ion battery anode materials. We report the (de)lithiation behavior of two WR-derived layered niobates: NaNb3 O8 and KNb3 O8 . Both demonstrate multi-electron (Nb 5+ /Nb 3+ ) redox on the first discharge, reacting with ≈5 mol Li per mol A Nb3 O8 . Li intercalation in NaNb3 O8 is dominated by Li-diffusion kinetics and evolution of the interlayer structure, with Li initially filling octahedral sites near the interlayer space to draw the layers together to form a (2 × 2) ∞ WR structure. This average structure change pushes Na ions into the square channels, blocking fast Li diffusion down the square channels that provide the fast Li-ion conduction in most WR materials. Upon charge, Li ions incorporated into the octahedral WR sites (ordered vacancies in the layered structure) are extracted, revealing a new, reversible Li site for additional capacity in WR-like materials. The behavior of KNb3 O8 is similar, but has additional hysteresis associated with its larger counter-cation. While neither layered niobate matches the demonstrated performance of WR materials, by studying them, we identify a route for increased capacity in WR-like frameworks. Additionally, we identify the important role of Li diffusion kinetics and counter-cations in the cycling behavior of WR-derived structures.